DISTAL PENILE FASCIOCUTANEOUS FLAP FOR STRICTURE DISEASE OF ANTERIOR URETHRA - Ihsan Ullah Khan; Farakh Ahmed Khan (Journal of University Medical & Dental College, 2012)
ABSTRACT Objectives: To develop curative treatment for complex stricture disease involving anterior urethra. Patients and methods: A series of 20 patients with a median age of 35 years with history of repeated optical internal urethrotomies >5, underwent surgery. Stricture site and length was evaluated by Retrograde and Antegrade urethrogram. Stricture calibration was done by retrograde ureteric catheter insertion of variable sizes. Onlay or tubular flap applied over partial or blind stricture respectively ranging from 5 cm to 15 cm. Results: Period of follow up 24 months. Complications like patchy necrosis of penile skin (3) ext. meatal stenosis (2), Fistula (1) stricture at anastomotic site (1) and post void dribbling (5) were noted. Patient’s quality of life improved. Conclusion: Distal penile fasciocutaneous flap is effective tool for recurrent stricture disease involving anterior urethra.